DIMENSI-DIMENSI BUDAYA ORGANISASI DI INDONESIA - Angela Oktavia Suryani (MANASA, 2012)
Organizational culture is a central of organizational daily practice and guidance to organizational success. The current research aimed o identify Indonesian organization culture, included involved 341 participants who came from organizations in four industrial cities in Indonesia, namely Bandung, Denpasar, Jkarta, and Yogyakarta. The data contaminated with response bias; subjective standardized-scores method was used to overcome this problem. The result showed similiarities with the result from GLOBE study that the Indonesian employees were practicing humane orientation, collectivism, less assertive, and less the Indonesian employees were pranticing humane orientation, collectivism, less assertive, and less appreciating gender egalitarianism. In the measurement of ideal culutre, there were similiarities and differences with result of GLOBE study. The similarities were that the Indonesian employees were expecting higher future orientation and lower power distance, whereas the differences were that they expecting lower assertiveness and collectivism.